Addressing loneliness in emerging adults in primary care: a pilot feasibility study - Ma, Kris Pui Kwan; Keiser, Brennan; Garcia, Melissa; Hsu, Chialing; Cortez, Karina; Johnson, Ashley; Pleho, Ajla; Curran, Mary C.; Schloredt, Kelly; Chan, Kwun C. G.; Stephens, Kari A.; Tong, Sebastian T. (Frontiers in Psychiatry, 2025)
IntroductionLoneliness among emerging adults is common and is associated with poor physical and mental health. Most loneliness interventions have not been adapted nor tested in primary care that can broadly reach this population. This study aims to pilot test the feasibility, acceptability, and preliminary impact of two adapted interventions –cognitive behavioral therapy (CBT) and social prescribing (SP) – on reducing loneliness in emerging adults in primary care.MethodsParticipants aged 18-25, who were seen in primary care and met the cut-off score on the UCLA-3 loneliness, were assigned to either CBT (N=6) or SP (N=9). Both group interventions were delivered virtually for five weeks. Outcomes included the 20-item UCLA loneliness scale, PHQ-9 depression, and GAD-7 anxiety. Ten qualitative interviews were conducted to understand participants’ experience of the interventions and effects on their loneliness.ResultsOf 15 participants (11 women, mean age = 22), 14 of them completed either intervention. Results from paired T-tests showed pre-post reductions in loneliness, depression, and anxiety for both CBT and SP interventions, though they were statistically non-significant. Four themes described participants’ i) experience of loneliness, ii) changes in self and behavior, iii) barriers and facilitators to participation, and iv) suggestions for intervention adaptations.DiscussionsThe results suggest that it may be feasible to treat loneliness in emerging adults in primary care with adapted interventions like CBT and SP. Further research with larger sample sizes and pragmatic, randomized controlled trial designs are needed to test the effectiveness of these interventions in primary care settings.